Maturam frugem flore manente ferens: pochwała starości w poezjach Auzoniusza - Krynicka, Tatiana (Vox Patrum, 2011)
Decimus Ausonius Magnus (ca 310-394) was a rhetorician, a teacher, a tutor of young Gratian and a highly-ranked, influential official, as well as one of the most famous poets of the late Roman Empire. In his poems, he frequently described the small world he belonged to, the daily routine of his own, of his relatives, professional colleagues and friends. As the poet reached his old age, he made it a subject of his poetry. Ausonius considers old age to be a blessing, a time which permits a wise, generous person to gather fruit of his good deeds and fulfilled duties, to watch children and grandchildren grow and achieve successes, to share one’s wisdom with younger persons. Ausonius shows his grandfather and his grandmother, his aunts, but first of all his father, Ausonius senior, as the examples of happy old persons, loving and loved, respected and needed by the people who surrounded them. He notices that old persons can be joyful, healthy and beautiful. Writing about old age, he mentions illness only once, while expressing his joy of having recovered and being able to send greetings to the grandson who celebrates his birthday. In spite of his age, Ausonius still loves his wife Sabina, who died many years before, the same way as he loved her when he was a young husband. He is deeply attached to Bissula, the charming German girl captured and given to him by the Emperor Valentinian I probably circa 368. Besides, he really enjoys spending time with his friends and with the Muses. In his epigrams, most of which don’t have personal, but rather literary character, the poet translates, quotes, paraphrases and imitates Greek and Latin epigrams which deal with the theme of old age. Although in Ausonius’ poems exists an obvious resemblance to their models, he grants himself much freedom in his remouldings. Not only he alters circumstantial details, expands or abbreviates the original, bur also uses them as mere starting points of his reflexion. It becomes more important for him to ponder over quickly passing youth or over a lover’s feelings towards a woman who rejected him when she was young, but whom he still admires, than to play a literary game. Ausonius never parodies nor even portrays women trying to attire men in their old age, even though he may mock old men pretending to look younger than they are. Neither he complains about pains and sorrows of old age. In all that, he remains a true Roman and a true gentleman.